Uji Potensi Sari Buah Belimbing Wuluh (Averrhoa bilimbi L.) dalam Menghambat Pertumbuhan Bakteri Aeromonas salmonicida Smithia Secara In Vitro [Potential Test Cucumber Fruit Juice (Averrhoa bilimbi L.) In Inhibiting Growth Of Aeromonas salmonicida Smithia Bacteria By In Vitro] - Prayogo Prayogo; Boedi Setya Rahardja; Rena Wilis Putri (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract Giving antibiotics continuously can cause A. salmonicida smithia become resistant and residues of antibiotics may pollute the water environment. One alternative to using traditional medicinal plants that are antibacterial. Advantages of using traditional medicinal plants are relatively more secure, easily available, inexpensive, does not cause resistance, and relatively harmless to the surrounding environment. The content of natural chemicals from cucumber fruit is known to have antibacterial effects namely, flavonoids and phenols. The purpose of this study to determine ability the cucumber fruit juice inhibit bacterial growth A. salmonicida smithia and to determine the best concentration to inhibit bacterial growth A. salmonicida smithia with ampicillin drugs for comparison by in vitro. This research was conducted in the Bacteriology Laboratory of Fish Quarantine Center of Sidoarjo and Human Genetic Laboratory the Institute of Tropical Disease Centre, Airlangga University, Surabaya. This research use done eksperimental method by in vitro, with a large measure of cucumber fruit juice inhibition zone around the existing paper disc and comparing it to a large zone of inhibition using ampicillin. Concentration dilution series cucumber fruit juice used during the research, began 2 gr/ 2 ml to the concentration of 0,0625 gr/ml. Result of research show at concentration 0,125 gr/ml still has ability to pursue bacterium A. smithia salmonicida, so that can be anticipated that effective cucumber fruit juice if used as by drug, because at small concentration can to pursue bacteria A. smithia salmonicida by in vitro.